THE IMPORTANCE OF THE CORRELATION BETWEEN AGREEMENTS OF CIS MEMBER STATES AND NATIONAL LEGISLATION IN THE EXECUTION OF THE JUDICIAL DECISIONS (FOR EXAMPLES OF JUDICIAL PRACTICE OF THE CIS ECONOMIC COURT) - Evelyn Nikolaevna, Нагорная; Tatiana Nikolaevna, Зацепина (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article analyzes the practice of the CIS Economic Court on the interpretation of international treaties CIS regulating the recognition and enforcement of foreign judgments. The authors stress that the court acts CIS Economic Court reveal the problematic issues of application of the agreements and establish (offer) ways to solve its.